Comparison of efficacy and safety of tenofovir and entecavir in chronic hepatitis B virus infection: a systematic review and meta-analysis. - Weixia Ke; Li Liu; Chi Zhang; Xiaohua Ye; Yanhui Gao; Shudong Zhou; Yi Yang (PLoS ONE)
Objective Tenofovir (TDF) and entecavir (ETV) are both potent antiviral agents for the treatment of chronic hepatitis B virus (HBV) infection. Multiple studies have compared efficacy and safety of these two agents, but yielded inconsistent results. Hence, we conducted a meta-analysis to discern comparative efficacy and safety. Methods Published data relevant to a comparison of TDF and ETV used in HBV were included. HBV DNA suppression rate, ALT normalization rate, and HBeAg seroconversion rate at 24 weeks and 48 weeks were reviewed. Drug safety profiles and resistance were also discussed. Results Seven articles met entry criteria. Four and six articles included data for 24 and 48-week HBV DNA suppression rates, respectively, and no significant differences for the rates between the two drugs were found in chronic HBV patients (TDF vs. ETV: relative risk [RR] = 1.10, 95% CI = 0.91-1.33 and RR = 1.07, 95% CI = 0.99-1.17 for 24 weeks and 48 weeks, respectively). For the ALT normalization rate (three studies for 24 weeks, four articles for 48 weeks) and HBeAg seroconversion rate (two and four studies for 24 weeks and 48 weeks, respectively), no difference was observed between TDF and ETV. Additionally, no significant distinction in short term safety was found for CHB patients. Conclusions TDF and ETV are similarly effective and safe in chronic HBV patients after 24 weeks and 48 weeks of anti-viral therapy. Nevertheless, the long-term efficacy and safety of TDF and ETV should be monitored in prolonged therapy.